Research, standards, practice: Necessary conditions for occupant-centric indoor environments - Berger, Christiane; Bochukova, Veselina; Mahdavi, Ardeshir (CLIMA 2022 conference, 2022)
The precise definition of appropriate indoor-environmental conditions for human occupancy is not trivial. Practitioners in the building delivery process frequently rely on applicable standards and guidelines to identify the relevant performance variables and their required values. In this context, recent inquiries have pointed out a number of gaps in our knowledge. Certain aspects of these gaps can be explored in terms of the following three basic questions: i) Are current codes/standards compliance processes limited to meeting formal criteria and minimum requirements, thereby losing sight of the essential task of producing high-quality indoor environments? ii) Do currently deployed standards entail a clear, transparent, and evidence-based logic underneath their recommended or mandated quality requirements? In other words, have the results of scientific research on indoor environment been adequately translated into the language of codes and standards? iii) What is the degree of precision and validity of the indoor-environmental research results? In other words, are we asking the right questions and using the right methods to answer them? To address these questions, the present contribution considers a number of common indoor-environmental quality standards pertaining to thermal and visual comfort, as well as indoor air quality. The outcome of this preliminary appraisal point to gaps in the chain of evidence from research to standards. The results also point to a number of areas in which the scientific research on indoor-environmental quality could benefit from a strategic rethinking of a number of its underlying methodological premises.